Biomonitoring genetic instability in normal healthy population using a simple cytogenetic marker – micronucleus test - Anuradha Yadav1 and Dr Rajeswari Narayanappa2, Usha Veerachari1*, Shilpa Venkatesh1 (International Multidisciplinary Research Journal, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Micronuclei in epithelial cells are widely used as biomarkers for monitoring genetic instability in humans. In this study, we have evaluated the buccal cells of 144 normal healthy individuals. The frequency of micronuclei was analysed and their relationship to different confounding factors (age, gender, diet and life style habits) was determined. The results show a significant increase in the observed frequency of micronuclei with respect to age. Males show a comparatively high percentage of micronuclei. Non-vegetarian diet, smoking and alcohol consumption are also suggestively significant.